Nano-composite, preparation method and application of nano-composite to sensitizer

By preparing the two-dimensional defective nanocomplex mPEG-Bi2O3 in oxygen vacancies, the problem of hypoxic environment limitation in radiotherapy and acoustic dynamic therapy is solved, more efficient cancer treatment effect is achieved, and the stability of nanocomplexes is improved and Security.

CN119139468APending Publication Date: 2024-12-17THE SECOND AFFILIATED HOSPITAL OF CHONGQING MEDICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411312173.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing radiation therapy and acoustic dynamic therapy have radioresistance and hypoxic environment limitations when treating cancer, resulting in unsatisfactory treatment effects, and traditional Bi2O3 materials lack the acoustic dynamic therapeutic effect.

Method used

The two-dimensional defective nanocomposite mPEG-Bi2O3 with oxygen vacancies were prepared by vacuum ball milling and liquid phase ultrasonic peeling technology. The production of reactive oxygen species by in-situ catalyzing, improves the hypoxic state of the tumor microenvironment, and uses the X of the high atomic number bismuth Strong linear absorption improves the efficiency of radiation therapy.

Benefits of technology

The effects of acoustic dynamics and radiation therapy are significantly improved, and the synergistic effect is enhanced, the treatment effect is reduced, the damage to adjacent tissues is reduced, the circulation time of nanocomplexes in the body is extended, and the tumor targeting and safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119139468A_ABST
    Figure CN119139468A_ABST
Patent Text Reader

Abstract

The invention relates to the field of medicine, in particular to a nano-composite, a preparation method and application of the nano-composite to a sensitizer, the nano-composite comprises Bi2O3, the Bi2O3 is provided with oxygen vacancies, and the Bi2O3 is modified with PEG. The preparation method comprises the following steps: S1, carrying out vacuum ball milling on sodium bismuthate to obtain a first product; s2, mixing the first product, ultrapure water and PEG (Polyethylene Glycol), and dispersing by using an ultrasonic cleaner to obtain a second product; and S3, finally, crushing the second product in the step S2 by using an ultrasonic cell crusher to obtain the nano-composite. After the nanocomposite is applied to the sensitizer, the nanocomposite has the functions of a sound-sensitive agent and a radiotherapy sensitizer. Through the scheme of the invention, the sonodynamic therapy effect is enhanced, the radiation resistance is reduced, and the radiation therapy effect is improved. Moreover, according to the scheme of the invention, the sonodynamic therapy and the radiation therapy can be combined, and the sonodynamic therapy and the radiation therapy can be used for cooperative therapy, so that the effect is better than that of the traditional single sonodynamic therapy or radiation therapy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medicine, and in particular to a nanocomposite, a preparation method and application of the nanocomposite in a sensitizer. Background Art

[0002] Cancer has become a global malignant disease. Currently, there are many treatments for cancer. Traditional treatments such as surgery are not ideal. The rapid development of nanotechnology has opened a new chapter in nanomedicine. New cancer therapies based on reactive oxygen species (ROS) have emerged, including but not limited to photodynamic therapy, sonodynamic therapy, radiotherapy and chemodynamic therapy.

[0003] Among them, radiotherapy is currently one of the effective therapies to eliminate cancer cells and overcome cancer recurrence, but high-dose radiation inevitably causes collateral damage to adjacent tissues, which can eventually lead to severe systemic toxicity and immunosuppression in patients. In addition, the tumor microenvironment is the internal environment in which tumor cells survive, and it has the characteristics of hypoxia, slight acidity, high concentration of hydrogen peroxide, reducing environment, and high vascular permeability. Tumor microenvironment hypoxia is an inherent characteristic of solid tumors, and hypoxia can lead to radiation resistance, thereby limiting the ultimate therapeutic effect of radiotherapy. Therefore, the development of safe and efficient new radiosensitizers is a major need in clinical tumor treatment.

[0004] Sonodynamic therapy is an emerging non-invasive tumor treatment method that has developed rapidly in recent years. It is a new treatment method that uses ultrasound to stimulate sonosensitizers to produce highly cytotoxic reactive oxygen species, thereby killing tumor cells. Compared with existing photodynamic therapy technology, sonodynamic therapy has better tissue penetration ability, so it has greater advantages in the field of tumor treatment. However, the efficacy of single sonodynamic therapy is limited. There is a disadvantage that the sonosensitizer itself has a low efficiency. In addition, the hypoxic and highly reducing tumor microenvironment severely limits its therapeutic effect. Therefore, the development of new sonosensitizers with high sonosensitivity is also a major demand for clinical tumor treatment. Summary of the invention

[0005] The present invention is intended to provide a nanocomposite, a preparation method and an application in a sensitizer to enhance the effect of sonodynamic therapy, while reducing radiation resistance and improving the effect of radiotherapy. In addition, through the present application scheme, sonodynamic therapy and radiotherapy can be combined to achieve a synergistic treatment of ultrasound and radiation, which is better than traditional single sonodynamic or radiotherapy.

[0006] To achieve the above object, the present invention adopts the following technical solution: a nanocomposite comprising Bi2O3, wherein the Bi2O3 has oxygen vacancies to form a two-dimensional defect material, and the Bi2O3 is modified with PEG.

[0007] After reviewing the literature, the inventor noticed that the research on bismuth-based materials is receiving widespread attention, especially bismuth oxide (Bi2O3) in the fields of chemical industry, glass manufacturing, electronics, coatings and medicine (it has multiple medicinal effects such as antibacterial, anti-inflammatory, and hemostatic effects, and has been widely used in clinical treatment). In view of this, the inventor conducted in-depth research on Bi2O3 and found in preliminary experiments that it has sonodynamic properties (sound dynamics is an emerging research field based on photodynamics in recent years, with relatively few related studies and applications, and no researchers have been found to explore the sonodynamic properties of Bi2O3). This key discovery stimulated the inventor's interest in continuing research and became the starting point for subsequent work.

[0008] Based on this, the inventors used a method combining vacuum ball milling and liquid phase ultrasonic exfoliation technology to successfully prepare a two-dimensional defect material with oxygen vacancies: mPEG-Bi2O3. Through further experimental verification, this two-dimensional material containing oxygen vacancies significantly improved the ability of Bi2O3 to produce reactive oxygen species (ROS) by sonodynamics, which helps to improve the hypoxic state in the tumor microenvironment. In addition, under oxygen-rich conditions, the material can further enhance the effect of sonodynamic / radiotherapy, activate anti-tumor immune response, and achieve long-term therapeutic effects.

[0009] The principles and advantages of this application scheme are: 1. The nanocomposite in the present application improves the effect of sonodynamic therapy: the traditional Bi2O3 material does not have oxygen vacancies, and the traditional Bi2O3 material does not have the effect of sonodynamic therapy or the sonodynamic therapy effect is limited. In the present application, the inventor sets oxygen vacancies on the nanocomposite, and the role of oxygen vacancies is to reduce the band gap. In this way, the nanocomposite can produce more reactive oxygen under ultrasonic activation through in-situ catalytic hydrogen peroxide (low-intensity focused ultrasound LIFU promotes electron-hole separation, holes oxidize water, produce hydroxyl free radicals, and cause oxidative stress). Reactive oxygen improves the ability of sonodynamic therapy to produce superoxide anions and quickly replenishes oxygen that depends on reactive oxygen. At the same time, mPEG-Bi2O3 can continuously consume the level of reduced glutathione (GSH) in the tumor microenvironment, thereby preventing the generated reactive oxygen from being consumed by GSH. In this way, the oxidative stress of cells is amplified by increasing the reactive oxygen in tumor cells and depleting the reactive oxygen scavenger glutathione in cells, thereby improving the effect of sonodynamic therapy.

[0010] In addition, the nanocomposite in the present application can catalyze hydrogen peroxide to produce oxygen, and continuously provide substrate for ultrasonic catalysis, thereby increasing the oxygen enrichment in the tumor site, destroying the tumor microenvironment, alleviating the hypoxic environment, and reducing the restrictions on the effect of sonodynamic therapy, thereby improving the effect of sonodynamic therapy.

[0011] 2. The nanocomposite of the present application has a radiotherapy effect. The nanocomposite of the present application utilizes the strong absorption of X-rays by high atomic number bismuth, which reduces the radiation dosage, improves the radiation efficiency, and thus improves the effect of radiotherapy. After the radiation dosage is reduced, the collateral damage to adjacent tissues is reduced, and the generation of severe systemic toxicity and immunosuppression is reduced or avoided.

[0012] 3. The radiotherapy effect and sonodynamic therapy effect of the nanocomposite of the present application have a synergistic effect (better than the simple superposition of radiotherapy and sonodynamic therapy). The nanocomposite of the present application can catalyze the production of oxygen in situ, improve the tumor microenvironment, enhance the sonodynamic therapy effect, and relieve the hypoxic environment, which is conducive to reducing radiation resistance and improving the effect of radiotherapy.

[0013] The nanocomposite of the present application has both radiotherapy and sonodynamic therapy effects, and adopts synergistic treatment of both ultrasound and radiation, which is better than traditional single sonodynamic or radiotherapy and has great clinical transformation application value.

[0014] 4. The nanocomposite in this application has low toxicity, is cheaper and safer than other heavy metals such as high atomic number systems (such as gold).

[0015] 5. The nanocomplex of the present application can reshape the tumor microenvironment, activate anti-tumor immunotherapy, and have a long-term anti-tumor effect.

[0016] 6. Unmodified Bi2O3 has a short circulation time in the body and cannot effectively reach the tumor target, resulting in poor therapeutic effect. However, the PEG modification in this application on Bi2O3 prolongs the clearance half-life of the nanocomplex in the body, reduces the possibility of being phagocytosed by macrophages, prolongs its retention time in the blood circulation, and improves its stability in plasma, which is beneficial to tumor targeting. By utilizing the EPR effect (EPR effect, i.e., the enhanced permeability and retention effect of solid tumors, refers to the property that molecules or particles of certain sizes tend to accumulate in tumor tissues relative to normal tissues), the nanocomplex is more easily enriched in tumor cells, the nanocomplex is aggregated together, and the time for the nanocomplex to act on tumor cells is prolonged, thereby ensuring the therapeutic effect.

[0017] Preferably, as an improvement, the weight ratio of Bi2O3 to PEG is 3:20. Thus, this ratio can ensure the PEG modification amount, ensure the modification effect of Bi2O3, and thus ensure the therapeutic effect of the nanocomposite.

[0018] Preferably, as an improvement, PEG is DSPE-PEG 2000(Methoxy polyethylene glycol phospholipid, molecular weight 2000).

[0019] In this protocol, the PEG we used was DSPE-PEG 2000 , which is a monomethoxy polyethylene glycol (mPEG) with the characteristics of polyethylene glycol with a single terminal hydroxyl group. 2000 The modification of the material can avoid the situation where Bi2O3 material is directly connected to PEG and then PEG forms a connection with Bi2O3 material compared to other types of PEG, thereby preventing the formation of a colloid-like structure, which is not conducive to the treatment of diseases.

[0020] Preferably, as an improvement, Bi2O3 is in the form of flakes. The flake structure has a narrower band gap, which effectively promotes the separation of electron-hole pairs. Since holes have strong oxidizing properties, they can more effectively convert H2O2 in the tumor microenvironment into hydroxyl radicals (·OH) with high cytotoxicity.

[0021] To achieve the above object, the present invention adopts the following technical solution: a method for preparing a nanocomposite, comprising the following steps: S1, ball milling, vacuum ball milling the sodium bismuthate to obtain the first product; S2, mixing the first product, ultrapure water and PEG modifier, and then dispersing them with an ultrasonic cleaner to obtain a second product; S3. Finally, the second product in S2 is crushed by an ultrasonic cell crusher. This step is carried out in an ice bath controlled preparation system. The temperature of the preparation system is controlled by an ice bath to be lower than 20° C., and a nanocomposite is finally obtained.

[0022] Therefore, the present application provides the above-mentioned preparation method, so that the flaky Bi2O3 in the present application can be prepared. Other conventional preparation methods cannot form oxygen vacancies on the material. If oxygen vacancies cannot be formed, the sonodynamic therapy effect and radiotherapy effect of the prepared nanocomposite cannot be guaranteed.

[0023] The ball milling in S1 and the ultrasonic dispersion in S2 are both for reducing the particle size at the beginning, and the ultimate goal is to reduce the hydrated particle size to below 280nm. Then, ultrasonic waves with high power density are used in S3 to disorder the surface of the metal oxide, change the electronic structure and generate oxygen vacancies.

[0024] Preferably, as an improvement, the operation method of the ice bath controlled preparation system is: the second product is placed in a centrifuge tube, and then the centrifuge tube is inserted into the center of a beaker filled with and compacted ice cubes. Next, ice water is added to the beaker until all gaps are filled. Every 15 to 20 minutes, the melted water is poured out, the ice cubes are refilled and compacted, and then ice water is added again. This process needs to be repeated until the set processing time is reached. In this way, it can be ensured that the temperature during the ice bath process is maintained below 20°C.

[0025] The reason for ice bath is that the ultrasonic cell disruptor generates heat during operation. Since PEG is a liposome, high temperature will cause the chemical bonds on it to become unstable, which may lead to unsuccessful PEG modification or even denaturation failure. Therefore, ice bath can ensure the effectiveness of the PEG modification process.

[0026] Preferably, as an improvement, the working time of the ultrasonic cell disruptor is 6 hours, wherein the working time is 2 seconds and the rest time is 2 seconds, and the power is 600 W. The power is set to 600 W to avoid the power being too small and affecting the disruption effect.

[0027] Preferably, as an improvement, during the ball milling process, vacuum ball milling is performed for 8 hours with a maximum rotation speed of 120 rpm.

[0028] During the research and exploration process, the inventors initially used standard ball milling technology, but found that the particle size dispersion of ordinary ball milling could not meet the requirements. Subsequently, the inventors turned to vacuum ball milling technology, which improved the problem of particle size and dispersion to a certain extent. However, new challenges came with it: if the ball milling time is too short, the material cannot be fully ground; if the ball milling time is too long, the material may be over-ground, resulting in the so-called "grinding paste" phenomenon. This makes it difficult to satisfy the quality of the prepared nanocomposite materials. In order to solve these problems, the inventors carefully adjusted the key parameters in the ball milling process. By precisely controlling the ball milling time, the inventors successfully overcame the above difficulties. The main purpose of the use of vacuum ball milling technology is to reduce the particle size of the material, and ultimately achieved a significant reduction in the particle size of the material after ball milling and a uniformity in particle size distribution.

[0029] Preferably, as an improvement, the temperature in the ultrasonic cleaner is 10°C, the dispersion time is 30 minutes, and the power is 120W. Bismuth is a heavy metal, which is easily deposited to the bottom of the tube under the action of gravity. It is beneficial to PEG modification after dispersion by ultrasonic vibration. If the modification is carried out in agglomerates, the amount of modification will be too small to affect the effect. In this application, the ultrasonic cleaner is controlled within the above working parameters to ensure the quality effect of PEG modification.

[0030] Preferably, as an improvement, when using an ultrasonic cleaner for dispersion treatment, the mixed liquid in S2 should be taken out every 4 to 8 minutes and manually shaken 5 to 10 times, and then put back into the ultrasonic cleaner to continue the dispersion treatment until the predetermined time is reached.

[0031] In order to achieve the above object, the present invention adopts the following technical solution: application of a nanocomposite on a sensitizer, the sensitizer plays the role of both a sonosensitizer and a radiotherapy sensitizer.

[0032] Therefore, by using the nanocomplex in the present application as a sensitizer, the sensitizer has the functions of both a sonosensitizer and a radiotherapy sensitizer, and the sensitizer has a synergistic therapeutic effect of sonodynamic radiotherapy sensitization.

[0033] To achieve the above object, the present invention adopts the following technical solution: application of a nanocomposite in medicine for treating lung diseases.

[0034] Through research, the inventors found that nanocomplexes have good application prospects in the treatment of lung diseases and have better therapeutic effects on lung tumors. Therefore, nanocomplexes are applied to drugs for the treatment of lung diseases. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1-Figure 6 Schematic diagram of TEM characterization of the morphology, size, and elemental composition of the nanocomposite.

[0036] Figure 7 Schematic diagram of XPS characterization of the elemental valence state of Bi2O3 in the nanocomposite.

[0037] Figure 8 Schematic diagram of FTIR characterization of the presence of Bi2O3 surface stabilizer mPEG.

[0038] Fig. 9 Schematic diagram of the potential detection results of the nanocomposite.

[0039] Fig.10 Schematic diagram of the nanocomposite particle size detection results.

[0040] Fig.11 This is a schematic diagram of the DPBF fading test result curve for the ultrasound group and the non-ultrasound group in the in vitro experiment.

[0041] Fig.12 Schematic diagram of the curve of different concentrations of TMB experimental results.

[0042] Fig.13 Schematic diagram of the in situ H2O2 consumption curve of mPEG-Bi2O3 at different Ph values ​​to simulate the weakly acidic environment of the tumor and the normal body.

[0043] Fig.14 Schematic diagram of the GSH consumption curve of the DTNB experimental results.

[0044] Fig.15 Schematic diagram of cell survival rate after 4T1 cells were mixed with different concentrations of nanocomplexes.

[0045] Fig.16 Schematic diagram of intracellular GSH consumption in groups G1-G4.

[0046] Fig.17 Schematic diagram of the internalization of Dil-labeled mPEG-Bi2O3 in 4T1 cells observed under confocal laser scanning microscopy at different times (scale bar: 100μm).

[0047] Fig.18 This is a flow cytometry diagram of phagocytosis.

[0048] Fig.19 Schematic diagram of flow cytometry detection of reactive oxygen species generation in DCFH-labeled 4T1 cells after different group treatments.

[0049] Fig. 20 Schematic diagram of the tumor inhibition rate in the G1-G7 groups.

[0050] Fig.21 Schematic diagram of H&E and TUNEL staining of tumor sections.

[0051] Fig. 22 Actual photos of tumor sizes in groups G1-G7.

[0052] Fig.23 This is the absorption curve in the wavelength range of 200 nm-1100 nm. DETAILED DESCRIPTION

[0053] The following is further described in detail through specific implementation methods: A nanocomposite includes Bi2O3, Bi2O3 has oxygen vacancies to form a two-dimensional defect material, and Bi2O3 is modified with PEG. In this embodiment, the weight ratio of Bi2O3 to PEG is 3:20. In this embodiment, PEG is mPEG. Bi2O3 is in flake form.

[0054] This embodiment also discloses a method for preparing a nanocomposite, comprising the following steps: S1, ball milling, vacuum ball milling 30 mg of sodium bismuthate for 8 h at a maximum speed of 120 rpm to obtain the first product; S2, the first product, 40 mL of ultrapure water and 200 mg of mPEG modifier (mPEG is polyethylene glycol with only one terminal hydroxyl group. In this embodiment, mPEG is methoxy polyethylene glycol phospholipid with a molecular weight of 2000, abbreviated as DSPE-PEG) 2000 , of course, other mPEGs can also be selected in other embodiments) for mixing, and then dispersed in an ultrasonic cleaner to obtain a second product. In this embodiment, the temperature in the ultrasonic cleaner is 10°C, the dispersion time is 30 minutes, and the power is 120w. During the dispersion process of the ultrasonic cleaner, the centrifuge tube containing the article is taken out of the ultrasonic cleaner every 4 to 8 minutes and manually shaken 5-10 times and then put into the ultrasonic cleaner for dispersion until the time is up; S3. Finally, the second product in S2 is crushed by an ultrasonic cell crusher. The total working time of the ultrasonic cell crusher is 6 hours (during the working process, it works for 2 seconds and stops for 2 seconds, and the power is 600w). This step is carried out under the ice bath control preparation system to finally obtain a nanocomposite. The operation method of the ice bath control preparation system is as follows: the temperature of the ice bath control preparation system is lower than 20°C. Specifically, the second product is placed in a 50mL centrifuge tube, and the centrifuge tube is inserted in the center of a beaker filled with ice and compacted. The ice around the centrifuge tube is above the liquid level in the centrifuge tube. Water is added to fill the gap in the cup. After 15-20 minutes, the melted water around the centrifuge tube is poured out, and then the ice is filled and compacted, and then ice water is added; this operation is repeated continuously.

[0055] The nanocomposite prepared in this embodiment is applied to the sensitizer, which has the functions of both sonosensitizer and radiotherapy sensitizer. The specific principle is: in tumor tissue, the nanocomposite can generate reactive oxygen species under ultrasound activation through in-situ catalyzed hydrogen peroxide (low-intensity focused ultrasound LIFU promotes electron-hole separation, holes oxidize water, generate hydroxyl free radicals, and cause oxidative stress). Reactive oxygen species improve the ability of sonodynamic therapy to produce superoxide anions and quickly replenish oxygen that depends on reactive oxygen species. At the same time, mPEG-Bi2O3 can continuously consume the level of glutathione (GSH) in the microenvironment, thereby preventing the generated reactive oxygen species from being consumed by GSH. mPEG-Bi2O3 can catalyze hydrogen peroxide to produce oxygen, and continuously provide substrates for ultrasound catalysis, increase the oxygen enrichment in the tumor site, destroy the tumor microenvironment, and initiate immune responses to selectively destroy tumor cells with specific cancer antigens.

[0056] In addition, after the tumor microenvironment is destroyed, it can alleviate radiotherapy resistance, which has a positive effect on improving the effect of radiotherapy. At the same time, due to the strong absorption of X-rays by the high-valent bismuth element, the spiral electrons generated by high-energy ionization during radiotherapy using the Compton scattering principle can further improve the efficiency of radiotherapy.

[0057] At the same time, bismuth forms adducts with tumor DNA, blocking the repair and proliferation of tumor cells. LIFU irradiation realizes sonodynamic therapy, which can further synergistically enhance sonodynamic / radiotherapy under oxygen-rich conditions. Sonodynamic therapy and radiotherapy are carried out together to activate anti-tumor immunity and long-term treatment, ultimately inducing tumor cell death.

[0058] experiment The following part is a series of experiments conducted on the nanocomposite prepared by the preparation method of this embodiment to prove the properties of the nanocomposite and its related effects and functions.

[0059] 1. Experimental characterization of nanoparticle properties 1. Through the use of transmission electron microscopy to detect the nanocomposite, combined with Figure 1-Figure 4 As shown, an electron beam is used to penetrate the sample, and the material is magnified and imaged by an electron optical system, showing the morphology of the micro-region of bismuth trioxide from 500nm, 10nm, 5nm, and 200nm respectively. The photo shows that the material is in the form of flakes. Figure 5 and Figure 6 As shown, mapping indicates that the material contains O and Bi, and the particles are uniform and well dispersed.

[0060] 2. By using XPS to characterize the elemental valence state of bismuth trioxide in the nanocomposite, combined with Figure 7 As shown, it can be shown that the sample contains two atoms, O and Bi, and their corresponding valence states.

[0061] In addition, X-ray photoelectron spectroscopy (XPS) is one of the most widely used surface analysis methods and can provide valuable quantitative information on the chemical state of the nanocomposite surface. It can obtain information about 10 nm deep from the surface. Defects in the nanocomposite will change the bonding energy, which can be observed from shifted peaks or newly appeared peaks. Therefore, XPS can be used as an effective method to detect oxygen vacancies and defect sites in materials. By analyzing Figure 7 , from the rising peak in the figure, it can be seen that oxygen vacancies are formed.

[0062] 3. Combination Figure 8 As shown, the characteristic peaks of mPEG were displayed by using Fourier transform infrared spectrometer FTIR, indicating the presence of mPEG, a surface stabilizer for Bi2O3 in the nanocomposite, that is, it was successfully modified.

[0063] 4. Use DLS dynamic light scattering particle size analyzer and Zeta potential analyzer to analyze the particle size and surface electrical properties of Bi2O3 in nanocomposites in different solutions. Fig.10 As shown in the figure, the particle size of the nanocomposite is relatively consistent, concentrated around 155 nm. Fig. 9As shown, the Zeta potential shows that the material is negatively charged, indicating that it has a longer circulation time in the body and is not easily eliminated. In addition, the high Zeta potential means that the material has good dispersibility in aqueous solution and is not prone to aggregation, thus showing excellent stability.

[0064] 2. In vitro experiments 1. Combination Fig.11 As shown, a DPBF fading experiment was conducted under the following conditions: DPBF = 5 ppm, Bi2O3 = 20 ppm, pH = 7.3, and reaction time of 37°C for 30 min. Fig.11 It can be seen that the 420nm characteristic absorption peak of DPBF is reduced to 90% within 12 minutes under ultrasound; Bi2O3 has the ability to generate reactive oxygen species and has sonodynamic properties, and can be used for reactive oxygen therapy of cancer.

[0065] 2. Combination Fig.12 As shown, TMB experiments were conducted, and the experiments were divided into 7 groups. The dosage of mPEG-Bi2O3 in each group was: 0μg / ml, 60μl; 300μg / ml, 60μl; 600μg / ml, 60μl; 900μg / ml, 60μl; 1200μg / ml, 60μl; 1500μg / ml, 60μl; 1800μg / ml, 60μl. The dosage of TMB in each group was 8.3mM, 20μl. The dosage of H2O2 (PH5.5) in each group was 31.25μM, 400μl. During the experiment, each group of reagents was mixed evenly in a 50ml centrifuge tube. After 10 minutes of reaction, 100μl of the reaction solution was taken from each group and placed in a 96-well plate. The absorbance at 300-800nm ​​was measured using a microplate reader SpectraMax ID3 plate reader (Molecular devices, SanJose, CA, USA). The TMB experiment also proved that the material produced active oxygen under ultrasonic stimulation, and the color gradually darkened with increasing concentration.

[0066] 3. Combination Fig.13 As shown, to simulate the weakly acidic environment of the tumor and the pH conditions in the normal body, this experiment set two different pH values, which were 6 and 7.4 respectively. The amount of reagents used in each experiment is shown in the following table. During the experiment, each group of reagents was fully mixed in a 50 ml centrifuge tube, and then the oxygen content in the liquid was measured using a JPB-607A portable dissolved oxygen meter (data was recorded every 10 seconds). The final results showed that mPEG-Bi2O3 has the ability to consume H2O2 in situ.

[0067]

[0068] 4. Combination Fig.14As shown in the figure, a DTNB experiment was carried out. The specific experimental steps were as follows: DTNB (10mM, 30μl) + mPEG-Bi2O3 (1600μg / ml, 100μl) + GSH (800μM, 900μl) were mixed evenly in a 1.5ml ep tube at pH7.4, and 100μl of the reaction solution was placed in a 96-well plate at different time points (0, 2, 4, 8, 20, 24, 48h). The microplate reader SpectraMax ID3plate reader (Molecular devices, San Jose, CA, USA) was used for measurement in the scanning range of 300-600nm. The consumption of GSH was detected by the attenuation of the characteristic absorption peak of DTNB at 412 nm. The results showed that GSH was consumed over time.

[0069] 3. Cell Experiment Select breast cancer cells (mouse) (4T1 cells), combined with Fig.15 As shown, the cells were co-cultured with nanocomposite materials at a concentration of 0-200 μmol / ml for 24 hours, and it was finally found that the survival rate was more than 80%, proving the safety of the nanocomposite materials.

[0070] Combination Fig.17 As shown, confocal laser scanning microscopy was used to observe the internalization of Dil-labeled mPEG-Bi2O3 in 4T1 cells at different times (scale: 100μm). In the confocal image after 4h incubation of mPEG-Bi2O3 nanomaterials with 4T1 cells, Dil-stained nanoparticles (red fluorescence) can be observed in the cytoplasm. In the control group without material incubation, only DAPI-stained cell nuclei (blue fluorescence) can be observed, indicating that the nanomaterial can be successfully taken up by 4T1 cells. At the same time, combined with Fig.18 As shown, the phagocytometric flow cytometer shows that the material can be gradually phagocytosed by cells as time goes by, and reaches a peak at 4 hours.

[0071] The experiment was divided into four groups, namely, group G1 (control group), group G2 (only mPEG-Bi2O3), group G3 (only ultrasound) and group G4 (mPEG-Bi2O3 and ultrasound together). The experimental results are shown in Fig.16 As shown, by comparing the groups, it can be seen that the GSH content in group G4 is the lowest, and group G4 consumes the most GSH, which shows that mPEG-Bi2O3 and ultrasound have a good effect in consuming GSH and have a good sonodynamic therapeutic effect.

[0072] Combination Fig.19As shown, flow cytometry was used to detect the reactive oxygen species generation of DCFH-labeled 4T1 cells after different group treatments, which indicated that mPEG-Bi2O3 and ultrasound acted together on cells to generate more reactive oxygen species and had a better sonodynamic therapy effect.

[0073] IV. In vivo experiment - breast cancer subcutaneous transplant model treatment experiment The specific steps of animal experiments are as follows: Step 1: In vivo safety assessment in mice Experimental female SPF BALB / c (7-8 weeks) were purchased from Chongqing Enbi Biotechnology Co., Ltd. Different doses of mPEG-Bi2O3 (0 mg / kg, 20 mg / kg, 40 mg / kg) were injected through the tail vein. The blood routine and blood biochemical indicators on the 1st, 14th and 28th days were used to evaluate the acute toxicity of the material and whether it damaged the hematopoietic function and liver and kidney toxicity of the animals.

[0074] The final result was that even at the highest dose, the body weight of the mice did not show any abnormal fluctuations during the 28-day observation period, and all blood biochemical and blood routine indicators remained within the normal range on day 28. In addition, histological sections of the main organs of the mice 28 days after injection were examined and stained with hematoxylin and eosin (H&E), and the results showed good biosafety and almost negligible systemic toxicity.

[0075] Step 2: Construction of mouse model First, the abdomen of BALB / c female mice was depilated and disinfected with cotton sprayed with 75% alcohol. Then, 100 μL of 4T1 cell suspension (1×10 6 When the tumor volume grows to 100 mm 3 Conduct follow-up experiments.

[0076] Step 3: ICP-MS analysis of element distribution in the body Tumor-bearing mice carrying 4T1 tumors were injected with mPEG-Bi2O3 (4.5 mg / mL, 200μL) through the tail vein. Different tissues (tumor, heart, liver, spleen, lung, kidney) were obtained at different times after injection (0, 1 h, 2 h, 6 h, 12 h, 24 h). The collected different tissues were weighed and digested with aqua regia for two days (hydrochloric acid: nitric acid = 3:1), and then heated at 75℃ for one day. The digested tissues were centrifuged (10000 rpm, 5 min) and diluted with 2% dilute nitric acid. Finally, ICP-MS was used to quantitatively analyze the Bi element in tumors and major organs. The in vivo metabolic pathways of the material and its distribution in tumors and organs were evaluated.

[0077] The final result is: tumor-bearing mice were injected with mPEG-Bi2O3 by tail vein for 24 hours and the ICP data were obtained: ① mPEG-Bi2O3 in the tumor site is basically stable at the plateau phase within 24 hours, indicating that mPEG-Bi2O3 can be effectively accumulated in the tumor site, providing a basis for determining the best time for treatment.

[0078] ② In six tissues including Heart, Liver, Spleen, Lung, Kidney and Tumor, it was found that mPEG-Bi2O3 was retained in lung tissue for a long time and in large doses, indicating that mPEG-Bi2O3 has better application prospects in the treatment of lung diseases.

[0079] Step 4: Intracorporeal sonodynamic therapy Will carry a breast cancer tumor (100 mm 3 ) were randomly divided into 7 groups (5 mice / group), namely ① saline ② simple US ③ mPEG-Bi2O3 ④ mPEG-Bi2O3 + US ⑤ simple X-ray treatment ⑥ mPEG-Bi2O3 + X-ray ⑦ mPEG-Bi2O3 + US + X-ray. For all groups receiving US treatment, the US conditions were set at a frequency of 1.0 MHz, a power density of 2.5 W / cm², a duty cycle of 50%, and an ultrasonic treatment time of 3 minutes; for all groups receiving X-ray irradiation, the dose was 10 Gy. Both saline and mPEG-Bi2O3 were injected at a concentration of 2 mg / ml in 200 μl (i.e., 20 mg / kg). US treatment was performed 4 hours after the injection of the material, and then the tumor volume (using a vernier caliper) and body weight changes (weighing) of each group of mice after different treatments were recorded every two days until the end of the 14-day treatment. The tumor volume is W 2 ×L / 2, (W is width, L is length). Tumor inhibition rate (%) = (1-experimental treatment group volume / Control group volume) × 100%. After the treatment is completed, different tissues are obtained, then fixed with tissue fixative, slices are made, and finally H&E staining is used. The survival rate of animals in different treatment groups is counted; the recurrence of tumors in different treatment groups is continuously observed; after the treatment is completed, tumors in each group are taken and their volumes are measured, photographed, and weighed. The final conclusion is: by observing the staining, the H&E staining of the main organs of each group of mice at different time points is basically the same, and the weight changes of all groups are similar. During the treatment, no obvious damage to the main organs was observed, which shows that the nanocomplex in this embodiment is safe in vivo. Combined with Fig. 20 As shown, from Fig. 20 , Fig. 22It can be seen that the mice with the smallest tumors are in Group 7, and the mice with the most obvious tumor inhibition are in Group 7, i.e., the mPEG-Bi2O3+ultrasound+radiotherapy group, which shows that the nanocomplex in this embodiment simultaneously exerts the effects of sonodynamic therapy and radiotherapy. Compared with Group 4 and Group 6, it can be clearly seen from the figure that the volume reduction of Group 7 (the volume reduction refers to the volume difference between Group 1 and the corresponding group) is greater than the sum of the volume reduction of Group 4 and Group 6, and the tumor treatment effect is the best.

[0080] Step 5: Immunohistochemical staining analysis After being treated in the same manner as in step 4, the collected tumors were embedded and sliced, and H&E and TUNEL staining were performed to verify the therapeutic effect. Fig.21 As shown in the figure, in the ros staining group, the cell nucleus of the DAPI channel is blue, and the positive CY3 channel (i.e., ROS dye) is red; in the TUNEL staining group, the cell nucleus stained by DAPI is blue under ultraviolet excitation, and the positive apoptotic cell nucleus is green; in the ki67 staining group, the cell nucleus of the DAPI channel is blue, and the positive Ki67 channel is red; the attached results show that in the mPEG-Bi2O3+US+RT group, the tumor tissue showed obvious apoptosis / necrosis. The degree of apoptosis and necrosis in the mPEG-Bi2O3+US+RT group was significantly higher than that in other treatment groups.

[0081] 5. Existing Bi2O3 (without oxygen vacancy structure) experiments The inventor purchased Bi2O3 on the market and conducted in vitro experiments. The experimental methods and conditions were based on the aforementioned in vitro experimental standards. The results showed that ordinary Bi2O3 did not have the ability to generate active oxygen, lacked sonodynamic effect, and could not consume H2O2 in situ, and the consumption of GSH was not observed.

[0082] In addition, the inventors found that the nanocomposite of the present application is also a good photosensitizer. By conducting an ultraviolet absorption experiment on the nanocomposite of this embodiment, the ultraviolet absorption experiment conditions are: Bi2O3=20 ppm, combined with Fig.23 As shown, the absorption curve in the wavelength range of 200 nm-1100 nm shows that this material can absorb the entire spectrum without characteristic absorption peaks, and is a very good photosensitizer.

[0083] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail here. It should be pointed out that for those skilled in the art, without departing from the technical solution of the present invention, several modifications and improvements can be made, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A nanocomposite comprising Bi2O3, characterized in that: The Bi2O3 has oxygen vacancies to form a two-dimensional defect material, and the Bi2O3 is modified with PEG.

2. A nanocomposite according to claim 1, characterized in that: The weight ratio of Bi2O3 to PEG is 3:

20.

3. A nanocomposite according to claim 1, characterized in that: The PEG is DSPE-PEG 2000 .

4. A method for preparing a nanocomposite according to any one of claims 1 to 3, characterized in that: The steps include: S1, ball milling, vacuum ball milling the sodium bismuthate to obtain the first product; S2, mixing the first product, ultrapure water and PEG modifier, and then dispersing them with an ultrasonic cleaner to obtain a second product; S3. Finally, the second product in S2 is crushed by an ultrasonic cell crusher. This step is carried out in an ice bath controlled preparation system. The temperature of the preparation system is controlled by an ice bath to be lower than 20° C., and a nanocomposite is finally obtained.

5. The method for preparing a nanocomposite according to claim 4, characterized in that: The operation method of the ice bath controlled preparation system is as follows: the second product is placed in a centrifuge tube, the centrifuge tube is inserted in the center of a beaker filled with ice and compacted, water is added to fill all the gaps in the cup, the melted water around the centrifuge tube is poured out every 15-20 minutes, and the compacted ice cubes are refilled, and ice water is added at the same time, and this operation is repeated continuously.

6. The method for preparing a nanocomposite according to claim 4, characterized in that: The working time of the ultrasonic cell disruptor is 6 hours, including 2s working and 2s resting, and the power is 600w.

7. The method for preparing a nanocomposite according to claim 4, characterized in that: During the vacuum ball milling process, the ball milling was performed for 8 h with a maximum speed of 120 rpm.

8. The method for preparing a nanocomposite according to claim 4, characterized in that: The temperature in the ultrasonic cleaner is 10°C, the dispersion time is 30 minutes, and the power is 120W.

9. Use of a nanocomposite according to any one of claims 1 to 3 on a sensitizer, characterized in that: The sensitizer has the functions of both sonosensitizer and radiotherapy sensitizer.

10. Use of a nanocomposite according to any one of claims 1 to 3 in medicine for treating lung diseases.